2023
DOI: 10.1002/advs.202301152
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy Augmented Piezo‐Sonosensitizer for Cancer Therapy

Abstract: Sonodynamic therapy (SDT) has been widely reported as a noninvasive and high‐penetration therapy for cancer; however, the design of an efficient sonosensitizer remains an urgent need. To address this issue, molybdenum disulfide nanoflowers (MoS2 NF) as piezo‐sonosensitizers and introduced sulfur vacancies on the MoS2 NF (Sv‐MoS2 NF) to improve their piezoelectric property for cancer therapy are designed. Under ultrasonic mechanical stress, the Sv‐MoS2 NF resulted in piezoelectric polarization and band tilting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…62 It belongs to the semiconductor category and has advantages such as good electron migration rate, direct band gap, low price, easy fabrication, and nontoxicity due to its noncentrosymmetric and piezoelectric effect. 63 More importantly, compared to other piezoelectric semiconductor sonosensitizers, Wu et al found that MoS 2 also exhibited specific biomimetic activity of glutathione (GSH) oxidases compared to BaTiO 3 , BiFeO 3 , ZnO, and many other piezoelectric materials, enabling it to effectively promote GSH oxidation, which is of great significance for tumor therapy. 64 3).…”
Section: Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…62 It belongs to the semiconductor category and has advantages such as good electron migration rate, direct band gap, low price, easy fabrication, and nontoxicity due to its noncentrosymmetric and piezoelectric effect. 63 More importantly, compared to other piezoelectric semiconductor sonosensitizers, Wu et al found that MoS 2 also exhibited specific biomimetic activity of glutathione (GSH) oxidases compared to BaTiO 3 , BiFeO 3 , ZnO, and many other piezoelectric materials, enabling it to effectively promote GSH oxidation, which is of great significance for tumor therapy. 64 3).…”
Section: Mosmentioning
confidence: 99%
“…Molybdenum disulfide was first synthesized in 2008, consisting of a molybdenum atom and a pair of atoms from the 16th column of the periodic table, including sulfur and selenium elements . It belongs to the semiconductor category and has advantages such as good electron migration rate, direct band gap, low price, easy fabrication, and nontoxicity due to its noncentrosymmetric and piezoelectric effect …”
Section: Piezoelectric Materials For Tumor Treatmentmentioning
confidence: 99%
“…11 Recently, some inorganic semiconductor materials exhibited good potential as sonosensitizers due to their good stability, long circulation time, and ease of functionalization, including TiO 2 , black phosphorus (BP), MoS 2 , etc. 12–14 However, the fast recombination of ultrasound (US)-excited electrons and holes resulted in unsatisfactory reactive oxygen species (ROS) generation efficiency, constraining their further application in clinics. 15 Therefore, it is urgent to develop a high-efficiency inorganic sonosensitizer for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%